Analysis Of Msme Actors' Perception Of Sharia Insurance As An Effort To Mitigate Business Risks (Case Study Of Msme Actors In Sukaramai Market Medan) - Siti Aisyah; Isnaini Harahap; Andri Soemitra (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the perception of Micro, Small, and Medium Enterprises (MSMEs) towards sharia insurance as an effort to mitigate business risks. This study was conducted at Sukaramai Market in Medan using a qualitative approach. The data was collected through in-depth interviews with MSME actors to understand the extent of their knowledge, understanding, and interest in sharia insurance products. The results of the study show that of a number of MSME actors interviewed, only five people have participated in sharia insurance. Sharia insurance participants generally have a better understanding of the benefits of business protection compared to those who do not follow insurance. The main factors that encourage participation in sharia insurance are the principle of halal, protection of businesses from unexpected risks, and the existence of a sense of fairness in the profit-sharing system. However, the majority of MSME actors who have not participated in sharia insurance admit that they do not understand the concept and benefits, and feel that there are financial limitations in paying premiums. This study recommends increasing socialization and education about sharia insurance so that more MSME actors are aware of the importance of business protection through this mechanism. The majority of MSME actors have a limited understanding of the concept of sharia insurance, even though they are aware of the importance of protecting against business risks.